Mapping the interrelationships between community assets. Issue 10 (25th August 2020) - McPherson, Matthew Q.; Friesner, Daniel; Bozman, Carl S.
Abstract : Purpose: Community asset mapping (CAM) is an evidence-based activity commonly used in local socioeconomic development initiatives. Residents and other stakeholders collaboratively identify the resources that they deem most important to the vitality of their community. Results are depicted qualitatively using maps. While maps are a useful means to convey information, alternate approaches to summarize data drawn from CAM activities may yield additional inferences that better inform community development initiatives. Design/methodology/approach: This study conducted a retrospective analysis of secondary, de-identified data collected from the 2015–2016 Gonzaga University Logan Neighborhood Asset Mapping Project. Hierarchical and nonhierarchical cluster analyses were used to establish interrelationships between the perceived importance of various community assets. Findings: The hierarchical cluster analysis revealed a very intuitive hierarchical clustering of community assets, with various health care services tightly clustered together. Similarly, farmers' markets, community gardens and meeting spaces were clustered closely together. Third, community education and care services for all age groups were clustered together. The nonhierarchical cluster analysis revealed intuitive clustering of respondent groups who valued particular sets of assets. Originality/value: By identifying these clusters and characterizing the linkages between them, it is possible to fund multiple development initiatives that are mutually reinforcing. For example, if the neighborhood obtains funds to invest, then they could be used to facilitate both community gardens and farmers' markets, two closely related activities. Additional physical locations might also be developed to support (possibly outdoor) meeting space. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-04-2020-0206 .